Interventions for self-harm in children and adolescents - Hawton, K; Witt, K; Taylor Salisbury, T; Arensman, E; Gunnell, D; Townsend, E; van Heeringen, K; Hazell, P (Royal College of Psychiatrists, 2016)
Self-harm (SH; intentional self-poisoning or self-injury) is common in children and adolescents, often repeated, and strongly associated with suicide. This is an update of a broader Cochrane review on psychosocial and pharmacological treatments for deliberate SH first published in 1998 and previously updated in 1999. We have now divided the review into three separate reviews; this review is focused on psychosocial and pharmacological interventions for SH in children and adolescents. This review is an abridged version of a Cochrane review previously published in the Cochrane Database of Systematic Reviews, 2015, Dec 21, Issue 12: CD012013.